Parahydrogen‐Induced Polarization in Hydrogenation Reactions Mediated by a Metal‐Free Catalyst. Issue 8 (19th January 2022) - Zakharov, Danila O.; Chernichenko, Konstantin; Sorochkina, Kristina; Yang, Shengjun; Telkki, Ville‐Veikko; Repo, Timo; Zhivonitko, Vladimir V.
Abstract: We report nuclear spin hyperpolarization of various alkenes achieved in alkyne hydrogenations with parahydrogen over a metal‐free hydroborane catalyst (HCAT). Being an intramolecular frustrated Lewis pair aminoborane, HCAT utilizes a non‐pairwise mechanism of H2 transfer to alkynes that normally prevents parahydrogen‐induced polarization (PHIP) from being observed. Nevertheless, the specific spin dynamics in catalytic intermediates leads to the hyperpolarization of predominantly one hydrogen in alkene. PHIP enabled the detection of important HCAT‐alkyne‐H2 intermediates through substantial 1 H, 11 B and 15 N signal enhancement and allowed advanced characterization of the catalytic process. Abstract : Substantial hyperpolarization of nuclear spins in alkene products was observed in alkyne hydrogenations with parahydrogen mediated by a metal‐free hydroborane catalyst. The observed effects are unusual, as the mechanism of the reaction is not pairwise, thus allowing hyperpolarization of only one of two protons at double bonds. Moreover, this enabled various important intermediates to be characterized by hyperpolarized 1 H, 11 B and 15 N NMR spectroscopy.